2022
DOI: 10.3389/fbioe.2022.843204
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Barefoot and Shod Populations Based on the Foot Metrics and Plantar Pressure Patterns

Abstract: The human being’s locomotion under the barefoot condition enables normal foot function and lower limb biomechanical performance from a biological evolution perspective. No study has demonstrated the specific differences between habitually barefoot and shod cohorts based on foot morphology and dynamic plantar pressure during walking and running. The present study aimed to assess and classify foot metrics and dynamic plantar pressure patterns of barefoot and shod people via machine learning algorithms. One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Also, the midfoot shape metric (artificial intelligence) was associated with lateral forefoot pressures during walking in both habitually barefoot and shod populations. An improved predictive statistical model (support vector machine) also showed an increased prediction accuracy on the basis of the same data set ( Xiang et al, 2022a ). Rapid prediction of foot function from easily measured foot shape metrics may become the norm and extend into clinical diagnosis of foot pathologies and customized footwear development.…”
Section: Population-based Modeling Of Shapesmentioning
confidence: 99%
“…Also, the midfoot shape metric (artificial intelligence) was associated with lateral forefoot pressures during walking in both habitually barefoot and shod populations. An improved predictive statistical model (support vector machine) also showed an increased prediction accuracy on the basis of the same data set ( Xiang et al, 2022a ). Rapid prediction of foot function from easily measured foot shape metrics may become the norm and extend into clinical diagnosis of foot pathologies and customized footwear development.…”
Section: Population-based Modeling Of Shapesmentioning
confidence: 99%
“…Understanding the role of external TA in both external impact loading and internal tibial bone loading, therefore, becomes crucial ( Matijevich et al, 2019 ). Enhancing the evaluation of these factors through machine learning not only presents an intriguing area of research but also holds substantial potential implications for future applications in sports medicine, injury prevention, and rehabilitation strategies ( Zadpoor and Nikooyan, 2011 ; Johnson C. D. et al, 2020 ; Xiang et al, 2022a ; Xiang et al, 2022b ; Gao et al, 2023 ; Lloyd et al, 2023 ; Uhlrich et al, 2023 ; Xiang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral limb asymmetry may not be evident during the initial stages of running but may arise as muscle fatigue and/or exercise intensity changes ( Arampatzis et al, 1999 ; Xiang et al, 2022a ). Mizrahi et al (2000) demonstrated that running-induced lower limb muscle fatigue increases the tibia’s vertical acceleration during heel strike, suggesting that more load accumulates in the shank after running fatigued.…”
Section: Introductionmentioning
confidence: 99%